Doctor Atomic - Adams, John 1947- (De Nederlandse Opera, 2007)
John Adams and Peter Sellars' opera about Robert Oppenheimer, at the Nederlandse Opera in Amsterdam. Which better subject John Adams and Peter Sellars could have chosen to denonciate the fall of the modern world? The atomic bomb and its inventor, Robert Oppenheimer (Gerald Finley), are in the middle of the action of this opera, which premiered in 2005 at the San Francisco Opera. After him, the world will never be the way it used to be, and is inexorably shifting towards the nuclear era. And yet, this opera focuses on common and universal problems, including love stories and broken hearts. The title of this opera reminds us of the famous movie by Stanley Kubrick (Dr. Strangelove: How I Learned to Stop Worrying and Love the Bomb), and features fantastic artists such as Gerald Finley who created the role in 2005: it is without any doubt a masterpiece which "modernizes" the issues on the lyric planet